MANAGEMENT PROCESS OF THE COMMUNAL POLICE OF THE CITY OF ZAJECAR - Manic, Aleksandar; Manić, Saška; Fokianos, Nikolaos (Journal of process management and new technologies, 2022)
Communal systems, as organizational units within local self-governments, are important factors in the organizational and executive structure of modern administration. Management has an important role with its supporting structures (finance and human resources) in every economy and business of the organization. Managing communal police is a difficult and demanding job, which requires a lot of knowledge, skills, understanding and experience in working with people. In practice as well as scientific research on work, it has been shown that joint work is always more efficient and effective than individual work. Numerous management theories have contributed, each in its own way, to improving the understanding of the factors that affect the efficiency of the organization as well as the motivation and satisfaction of employees on whom business efficiency directly depends. Since the work of communal police officers is work in pairs or in groups, the important role of the manager is to organize communal police officers and focus on solving the set tasks. As far as the authors know, there is no research regarding management process of the communal police in Serbia, therefore, the main goal of the paper is to present the management process of the communal police of the City of Zaječar.